Các kỹ thuật trợ giúp chứng minh bài toán hình học: cách tiếp cận trí tuệ nhân tạo - Thủy, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2016)
This paper investigates some fundamental techniques of  Artificial Intelligence for supporting geometry problem solving: Backward Inference and Forward inference over knowledge base, gathered from figures, theorems and AND/OR Grap representing rules. The proof process can be carried out either in “parkage mode” or in “stepwise mode”. A forward and backward inference algorithm for  predicate logics will be presented. Some  feature of an experimental system Geoprover are considered. This system is  implemented in C++, ver 3.1.